Building an urban park increases the intention of adults to practice physical activity - Raphaelly Machado Felix; Vinicius Martins Farias; Mauren Lúcia de Araújo Bergmann; Gabriel Gustavo Bergmann
Abstract Physical activity levels in adults are low and strategies should be put in place to change this. The aim of this study was to investigate whether building an urban park can increase adult neighborhood residents' intentions to partake in physical activity. In total, 395 adults living near where the park was being built participated in the study. The following information was collected: sociodemographic characteristics, current physical activity levels, and intention to use the park for physical activity. Around 80% of the subjects intended to use the park for physical activity. This frequency was higher among those who were classified as physically active and gradually higher as the distance between the home of the subject and the park decreased (p < 0.05). The offer of a public leisure space can contribute positively to changing population behavior related to regular physical activity.